2020
DOI: 10.1097/mbc.0000000000000949
|View full text |Cite
|
Sign up to set email alerts
|

‘Pulmonary thrombosis in situ’: risk factors, clinic characteristics and long-term evolution

Abstract: Pulmonary embolism typically occurs from deep venous thrombosis (DVT). However, not always a DVT can be identified, and ‘in situ’ generation of pulmonary embolism has been considered, referred to in the literature as ‘De novo pulmonary embolism’ (DNPE). The objective of the study is to assess risk factors, comorbidities, clinic characteristics and long-term evolution of patients with pulmonary embolism in the absence of an identified source. Retrospective study of 280 patients with pulmonary embolism, 190 pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…On the other hand, lung trauma and congenital or acquired abnormalities in lung structures are considered high risk factors of in situ PAT ( Van Gent et al, 2014 ; Fletcher-Sanfeliu et al, 2020 ) ( Figure 1 ). Experimental studies have shown that chest trauma may induce focal inflammation and dysfunction in pulmonary vascular endothelial cells, eliciting in situ PAT ( Knudson et al, 2011 ; Brakenridge et al, 2013 ) ( Figure 1 ).…”
Section: The Risk Factors Of Pulmonary Thromboembolism Associated With Deep Vein Thrombosis and Of In Situ Pulmonary Amentioning
confidence: 99%
“…On the other hand, lung trauma and congenital or acquired abnormalities in lung structures are considered high risk factors of in situ PAT ( Van Gent et al, 2014 ; Fletcher-Sanfeliu et al, 2020 ) ( Figure 1 ). Experimental studies have shown that chest trauma may induce focal inflammation and dysfunction in pulmonary vascular endothelial cells, eliciting in situ PAT ( Knudson et al, 2011 ; Brakenridge et al, 2013 ) ( Figure 1 ).…”
Section: The Risk Factors Of Pulmonary Thromboembolism Associated With Deep Vein Thrombosis and Of In Situ Pulmonary Amentioning
confidence: 99%
“…The factor V Leiden mutation is more strongly correlated to risk of DVT, 12 while cardiac diseases have been shown to be a stronger risk for PE, which might also be the case for pulmonary conditions such as chronic obstructive pulmonary disease (COPD). 12 , 13 Previous studies on differences are either small, 14 , 15 are exclusively based on old data, 5 , 12 , 16 or only evaluated a limited number of comorbidities. 13 , 17 Given the difference in severity and mortality between PE and DVT, there is a need for a large, comprehensive study focusing on differences between patients with PE and patients with DVT.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is not possible for us to definitively prove that the PE arose from an SST locus, we propose that there is a high likeli hood that the clot originated from the sigmoid given that these patients did not have any evidence of extremity DVT and had imaging demonstrating residual clot in the sigmoid. A de novo pulmonary embolism is another possibility; how ever, patients who develop de novo pulmonary embolisms often have multiple medical comorbidities, 26 which were not present in our patients.…”
Section: Discussionmentioning
confidence: 79%